2002
DOI: 10.1289/ehp.02110129
|View full text |Cite
|
Sign up to set email alerts
|

Public health consequences of mercury spills: Hazardous Substances Emergency Events Surveillance system, 1993-1998.

Abstract: We analyzed data from states that participated in the Hazardous Substances Emergency Events Surveillance (HSEES) system maintained by the Agency for Toxic Substances and Disease Registry to describe the public health consequences of mercury releases. From 1993 through 1998, HSEES captured 406 events in which mercury was the only substance released. Schools and universities, private residences, and health care facilities were the most frequent locations involved in mercury events, and human error was the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 2 publications
1
27
0
Order By: Relevance
“…14 Because mercury can easily become trapped in porous surfaces such as plaster or stucco interiors, carpeting, or cracks between tile or wood floors, it may persist in an indoor environment for several years. 1,15 The greatest human exposure hazard associated with elemental mercury is its vapor. Mercury vapor is heavier than air, and its concentration tends to remain high near its source.…”
Section: Cultural Use Of Mercury and Botanicasmentioning
confidence: 99%
“…14 Because mercury can easily become trapped in porous surfaces such as plaster or stucco interiors, carpeting, or cracks between tile or wood floors, it may persist in an indoor environment for several years. 1,15 The greatest human exposure hazard associated with elemental mercury is its vapor. Mercury vapor is heavier than air, and its concentration tends to remain high near its source.…”
Section: Cultural Use Of Mercury and Botanicasmentioning
confidence: 99%
“…However, the elemental (metallic) form of mercury can also affect the central nervous system and, like organic mercury, may be a concern for developmental effects in children (ATSDR 1999). Although dental amalgams are the primary source of elemental mercury exposure in the general population, releases of this metal from consumer products and devices (e.g., thermometers, barometers, thermostats, electrical switches, fluorescent lights, gas pressure regulators, batteries, and use of older latex paint) can also contribute to public exposures (Agocs et al 1990;Aronow et al 1990;ATSDR 1999ATSDR , 2000Zeitz et al 2002).…”
mentioning
confidence: 99%
“…Thus, environmental release of elemental mercury that results in human exposure can occur in many different locations [8]. Sarıkaya et al reported a case of acute elemental mercury poisoning that they followed presenting with abdominal pain, diarrhea and high fever.…”
Section: Discussionmentioning
confidence: 99%